Evaluation of Nasolacrimal Duct Obstruction in Chronic Rhinosinusitis Patients: A Clinical Study - Abdullah Naeem Syed, Dilshad Alam Khan, Rehan Moinuddin Shaikh, Ahsan Qureshi, Muhammad Shahzad Anwar, Muhammad Sharif Shahid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic rhinosinusitis (CRS) is a persistent inflammatory disorder of the nasal and paranasal sinuses that may extend toward adjacent anatomical structures, including the nasolacrimal drainage system. Secondary nasolacrimal duct obstruction (NLDO) is increasingly recognized as a potential complication of CRS, yet regional data remain limited. Objective: To evaluate the frequency, patterns, and clinical associations of nasolacrimal duct obstruction among patients with chronic rhinosinusitis presenting to tertiary eye care hospitals in Pakistan. Methods: This cross-sectional study was conducted at Al-Shifa Trust Eye Hospital, Rawalpindi, and Mughal Eye Hospital, Lahore, from January 2022 to May 2023. A total of 100 CRS patients aged 18–70 years were assessed through detailed ophthalmic examination, nasal endoscopy, fluorescein dye disappearance test, lacrimal syringing, and CT-PNS imaging. NLDO was categorized as partial or complete. Statistical analysis was performed using SPSS 26, with p < 0.05 considered significant. Results: NLDO was identified in 29% of CRS patients, of whom 48.3% had partial obstruction and 51.7% had complete obstruction. Patients with nasal polyps demonstrated a significantly higher prevalence of NLDO (43.7%) than those without polyps (22.1%; p = 0.01). Longer disease duration was also associated with increased obstruction, with 42.1% of patients symptomatic for >24 weeks affected. Radiological findings, including deviated nasal septum and concha bullosa, were more frequently observed in NLDO patients. Conclusion: Nasolacrimal duct obstruction is a common yet under-recognized complication in chronic rhinosinusitis. Its strong association with nasal polyposis, prolonged disease duration, and anatomical variations highlights the necessity for routine lacrimal assessment in CRS patients to ensure timely diagnosis and multidisciplinary management. Keywords: Chronic rhinosinusitis, Nasolacrimal duct obstruction, Epiphora, Nasal polyps, Dacryocystitis.